Instructional Supervision and Curriculum Integration as Drivers of Educational Quality: A Cross-Cultural Study - Buday, Danielle Loren; Galigao, Regina (Journal of Interdisciplinary Perspectives, 2025)
Persistent global inequalities in educational quality, teacher training, and school environment and resources remain as obstacles to student success and socioeconomic development. These issues are more severe in regions where instructional supervision and curriculum integration remain inconsistent. Existing studies have primarily examined instructional supervision and curriculum integration in isolation. However, there is a distinct gap in research exploring the combined impact of these factors on educational quality, especially in cross-cultural contexts. This study addresses that gap by analyzing how instructional supervision and curriculum alignment—viewed through the lens of Human Capital Theory—jointly impact educational quality and performance across various contexts. The objective is to investigate the synergistic effects of supervision and curriculum integration, with teacher training and school resources, on delivering high-quality learning experiences and supporting national development. Using a qualitative comparative method and data from Google Scholar (2020–2025), findings are arranged thematically: improving educational quality, higher education quality, teacher quality and training, and school environment and resources. Results show that collaborative oversight and curriculum alignment, backed by strong teacher development and sufficient resources, improve teaching quality, student engagement, and long-term success. Aligning higher education programs with job market needs also remains essential. The study concludes that a context-sensitive, theory-driven approach to oversight and curriculum helps bridge educational disparities and ensures the relevance of the workforce. Investments in adequate supervision, curriculum design, and teacher support yield lasting benefits for students and advance national progress, highlighting the pivotal role of education in developing human capital.